Optical laminate
The optical laminate addresses orange peel and warping issues by using thin adhesive layers and a reinforcing layer, enhancing display performance and durability under high humidity.
Patent Information
- Application Number
- KR1020220069846
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-07-29
- Filing Date
- 2022-06-09
- Publication Date
- 2026-11-05
- Estimated Expiration
- 2042-06-09
AI Technical Summary
Optical laminates in image display devices suffer from issues such as orange peel formation, scratches due to localized loads, and warping under high humidity conditions, which affect display performance.
An optical laminate design with specific thickness constraints for adhesive layers and inclusion of a reinforcing layer, along with phase difference layers, to suppress orange peel and warping while resisting localized loads.
The laminate effectively prevents orange peel, reduces light leakage, and maintains structural integrity under high humidity conditions by balancing adhesive layer thickness and incorporating a reinforcing layer.
Smart Images

Figure 112022060011703-PAT00003_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to an optical laminate. Background Technology
[0002] Recently, image display devices, such as liquid crystal display devices and electroluminescence (EL) display devices (e.g., organic EL display devices, inorganic EL display devices), have been rapidly becoming widespread. In image display devices, optical laminates are typically used, which include a polarizer and an optical functional layer (e.g., an anti-reflection layer, an anti-reflection layer). As such an optical laminate, a polarizer with an anti-reflection layer and an anti-reflection layer attached is known, for example (e.g., Patent Document 1). In a polarizer with an anti-reflection layer and an anti-reflection layer attached, an anti-reflection laminate including an anti-reflection layer is bonded to the viewing side of the polarizer through an adhesive layer, and an anti-reflection laminate including an anti-reflection layer is bonded to the viewing side of the anti-reflection laminate through an adhesive layer. However, in a polarizer with an anti-reflection layer and an anti-reflection layer attached, minute irregularities known as orange peel may form on the surface of the viewing side, which can adversely affect the display performance of the image display device.
[0003] In addition, localized loads may be applied to optical laminates used in image display devices. Depending on the configuration of the optical laminate, these localized loads may cause scratches on the polarizer, resulting in light leakage or bright spots (so-called white dots) in the image display device. Furthermore, optical laminates equipped with multiple optical functional layers have a problem in that they are prone to warping in high-humidity environments. Prior art literature
[0004] Japanese Patent Publication No. 2018-155998 The problem to be solved
[0005] The present invention is made to solve the above-mentioned conventional problems, and its main objective is to provide an optical laminate that can satisfy the suppression of orange peel, resistance to localized loads, and suppression of warping under high humidity environments in good balance. means of solving the problem
[0006] An optical laminate according to an embodiment of the present invention comprises a polarizing plate, a first optical functional body bonded to the viewing side of the polarizing plate through a first adhesive layer, a reinforcing layer bonded to the viewing side of the first optical functional body through a second adhesive layer, and a second optical functional body bonded to the viewing side of the reinforcing layer through a third adhesive layer, wherein the thickness of each of the first adhesive layer, the second adhesive layer, and the third adhesive layer is 17 μm or less, and the total sum of the thickness of the first optical functional body, the thickness of the reinforcing layer, and the thickness of the second optical functional body is 200 μm or less.
[0007] In one embodiment, the first optical functional body is a non-transparent laminate, and the non-transparent laminate includes a non-transparent layer in contact with the first adhesive layer and a first substrate disposed on the visible side of the non-transparent layer and in contact with the second adhesive layer.
[0008] In one embodiment, the second optical functional body is an anti-reflective laminate, and the anti-reflective laminate includes a second substrate in contact with the third adhesive layer, a hard coat layer disposed on the visible side of the second substrate, and an anti-reflective layer disposed on the visible side of the hard coat layer.
[0009] In one embodiment, the anti-reflective layer is located on the outermost surface of the optical laminate, and the moisture permeability of the anti-reflective layer is 0.1 g / mm 2 It is as follows.
[0010] In one embodiment, the polarizing plate includes a polarizer and a protective layer disposed on the viewing side of the polarizer and in contact with the first adhesive layer.
[0011] In one embodiment, the thickness of the polarizer is 10 μm or less.
[0012] In one embodiment, the optical laminate further comprises a first phase difference layer and a second phase difference layer arranged sequentially from the polarizer side on the side opposite to the viewing side of the polarizer, wherein the first phase difference layer exhibits a refractive index characteristic of nx > ny > nz and the second phase difference layer exhibits a refractive index characteristic of nz > nx > ny. Effects of the invention
[0013] According to an embodiment of the present invention, by making the thickness of each adhesive layer below the upper limit, forming a reinforcing layer between the first optical functional body and the second optical functional body, and making the total thickness of the first optical functional body, the reinforcing layer, and the second optical functional body below the upper limit, it is possible to realize an optical laminate that satisfies the suppression of orange peel, resistance to localized loads, and suppression of warping under high humidity environments in good balance. Brief explanation of the drawing
[0014] FIG. 1 is a schematic cross-sectional view of an optical laminate according to one embodiment of the present invention. Specific details for implementing the invention
[0015] Representative embodiments of the present invention will be described below, but the present invention is not limited to these embodiments.
[0016] (Definition of Terms and Symbols)
[0017] The definitions of terms and symbols in this specification are as follows.
[0018] (1) Refractive index (nx, ny, nz)
[0019] "nx" is the refractive index in the direction where the refractive index in the plane is maximum (i.e., the ground axis direction), "ny" is the refractive index in the direction perpendicular to the ground axis in the plane (i.e., the true axis direction), and "nz" is the refractive index in the thickness direction.
[0020] (2) In-plane phase difference (Re)
[0021] "Re(λ)" is the in-plane phase difference of the film measured with light of wavelength λ nm at 23°C. For example, "Re(450)" is the in-plane phase difference of the film measured with light of wavelength 450 nm at 23°C. Re(λ) is calculated by the formula: Re=(nx-ny)×d, where the thickness of the film is d(nm).
[0022] (3) Phase difference in the thickness direction (Rth)
[0023] "Rth(λ)" is the phase difference in the thickness direction of the film measured with light of wavelength λ nm at 23°C. For example, "Rth(450)" is the phase difference in the thickness direction of the film measured with light of wavelength 450 nm at 23°C. Rth(λ) is calculated by the formula: Rth=(nx-nz)×d when the film thickness is d(nm).
[0024] (4) Nz coefficient
[0025] The Nz coefficient is calculated by Nz = Rth / Re.
[0026] (5) Angle
[0027] In this specification, when referring to an angle, unless specifically stated otherwise, said angle includes angles in both clockwise and counterclockwise directions.
[0028] A. Overall composition of the optical laminate
[0029] FIG. 1 is a schematic cross-sectional view of an optical laminate according to one embodiment of the present invention. The optical laminate (1) of the illustrated example comprises a polarizing plate (2), a first optical functional body (3) bonded to the viewing side of the polarizing plate (2) through a first adhesive layer (61), a reinforcing layer (5) bonded to the viewing side of the first optical functional body (3) through a second adhesive layer (62), and a second optical functional body (4) bonded to the viewing side of the reinforcing layer (5) through a third adhesive layer (63). That is, the second optical functional body (4), the third adhesive layer (63), the reinforcing layer (5), the second adhesive layer (62), the first optical functional body (3), the first adhesive layer (61), and the polarizing plate (2) are laminated in this order from the viewing side of the optical laminate (1).
[0030] The thickness of each of the first adhesive layer (61), the second adhesive layer (62), and the third adhesive layer (63) is 17 μm or less, preferably 15 μm or less, and typically 5 μm or more. The first adhesive layer (61), the second adhesive layer (62), and the third adhesive layer (63) may have the same thickness or different thicknesses. In one embodiment of the present invention, the first adhesive layer (61), the second adhesive layer (62), and the third adhesive layer (63) have the same thickness.
[0031] The total thickness of the first optical functional body (3), the thickness of the reinforcing layer (5), and the thickness of the second optical functional body (4) is 200 μm or less, preferably 180 μm or less, more preferably 170 μm or less, and typically 140 μm or more.
[0032] Orange peel that forms on the viewing side surface of an optical laminate may be caused by irregularities in the adhesive layer. In this regard, with the above configuration, since the thickness of each adhesive layer is below the above upper limit, the irregularities in the adhesive layer can be suppressed from affecting the viewing side surface of the optical laminate, and the formation of orange peel on the viewing side surface of the optical laminate can be suppressed. However, if the thickness of each adhesive layer is below the above upper limit, there is a risk that the resistance of the optical laminate to localized loads may be reduced. In this regard, with the above configuration, since a reinforcing layer is formed between the first optical functional body and the second optical functional body, cracks do not occur even when a load exceeding a predetermined value is locally applied to the optical laminate, and as a result, an image display device in which light leakage and white dots are suppressed can be realized. In addition, since the total sum of the thickness of the first optical functional body, the thickness of the reinforcing layer, and the thickness of the second optical functional body is less than or equal to the above upper limit, even if a reinforcing layer is formed between the first optical functional body and the second optical functional body, the bending of the optical laminate under high humidity conditions can be suppressed. Therefore, it is possible to realize an optical laminate that satisfies the suppression of orange peel, resistance to localized loads, and suppression of bending under high humidity conditions in good balance.
[0033] In one embodiment of the present invention, the optical laminate (1) further comprises a first phase difference layer (7) and a second phase difference layer (8) arranged sequentially from the polarizer (2) side on the opposite side of the viewing side of the polarizer (2). The first phase difference layer (7) preferably exhibits a refractive index characteristic of nx > ny > nz. The second phase difference layer (8) preferably exhibits a refractive index characteristic of nz > nx > ny. According to this configuration, it is possible to impart a desired optical compensation function to the optical laminate (1).
[0034] In addition, in one embodiment of the present invention, the optical laminate (1) further comprises a panel-side adhesive layer (9). The panel-side adhesive layer (9) is disposed on the opposite side of the first phase difference layer (7) with respect to the second phase difference layer (8). When the optical laminate (1) comprises the panel-side adhesive layer (9), the optical laminate (1) can be attached to an image display cell by means of the panel-side adhesive layer (9).
[0035] In addition, in one embodiment of the present invention, the thickness of the optical laminate (1) is typically 330 μm or less, preferably 310 μm or less, more preferably 300 μm or less, and typically 250 μm or more, preferably 270 μm or more.
[0036] According to this configuration, since the thickness of the optical laminate (1) is below the upper limit, bending of the optical laminate under high humidity conditions can be stably suppressed. In addition, since the thickness of the optical laminate (1) is above the lower limit, cracking can be stably suppressed even when a load greater than a predetermined value is locally applied to the optical laminate.
[0037] The components of the optical laminate are described below.
[0038] B. Polarizing plate
[0039] In one embodiment of the present invention, the polarizing plate (2) comprises a polarizer (21) and a protective layer (22) disposed on the viewing side of the polarizer (21). The protective layer (22) is typically bonded to the viewing side of the polarizer (21) through any suitable adhesive layer (adhesive layer, pressure-sensitive adhesive layer: not shown). That is, the polarizing plate (2) may be composed of a polarizer (21), an adhesive layer, and a protective layer (22). The protective layer (22) is located between the polarizer (21) and the first pressure-sensitive adhesive layer (61) and is in contact with the first pressure-sensitive adhesive layer (61). The protective layer (22) is pressure-sensitively bonded to the first pressure-sensitive adhesive layer (61). Additionally, the polarizing plate (2) may further comprise a second protective layer on the side opposite to the viewing side of the polarizer (21).
[0040] B-1. Polarizer
[0041] Any suitable polarizer may be used as the polarizer (21). For example, the resin film forming the polarizer (2) may be a single-layer resin film or a laminate of two or more layers.
[0042] Specific examples of a polarizer composed of a single-layer resin film include a PVA-based resin film that has undergone iodine dyeing and stretching treatment (typically uniaxial stretching). The iodine dyeing is performed, for example, by immersing the PVA-based film in an aqueous iodine solution. The stretching ratio of the uniaxial stretching is preferably 3 to 7 times. Stretching may be performed after the dyeing treatment or while dyeing. Additionally, dyeing may be performed after stretching. If necessary, swelling treatment, crosslinking treatment, washing treatment, drying treatment, etc., are performed on the PVA-based resin film. For example, by immersing the PVA-based resin film in water and washing it before dyeing, not only can contamination or anti-blocking agents on the surface of the PVA-based film be cleaned, but the PVA-based resin film can also be swollen to prevent dyeing unevenness.
[0043] Specific examples of polarizers obtained using a laminate include a laminate of a resin substrate and a PVA-based resin layer (PVA-based resin film) laminated on the resin substrate, or a polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer applied and formed on the resin substrate. A polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer applied and formed on the resin substrate can be manufactured, for example, by applying a PVA-based resin solution to a resin substrate and drying it to form a PVA-based resin layer on the resin substrate to obtain a laminate of the resin substrate and the PVA-based resin layer; and stretching and dyeing the laminate to make the PVA-based resin layer a polarizer. In one embodiment of the present invention, preferably, a polyvinyl alcohol-based resin layer comprising a halide and a polyvinyl alcohol-based resin is formed on one side of the resin substrate. Stretching typically includes stretching the laminate by immersing it in an aqueous boric acid solution. In addition, the stretching may further include air-stretching the laminate at a high temperature (e.g., 95°C or higher) prior to stretching in an aqueous boric acid solution, if necessary. Furthermore, in one embodiment of the present invention, preferably, the laminate is subjected to a drying shrinkage treatment in which it shrinks by 2% or more in the width direction by heating while being conveyed in the longitudinal direction. Typically, the manufacturing method of the present embodiment includes performing an air-assisted stretching treatment, a dyeing treatment, an underwater stretching treatment, and a drying shrinkage treatment on the laminate in this order. By introducing assisted stretching, it becomes possible to increase the crystallinity of the PVA even when PVA is applied on a thermoplastic resin, thereby enabling the achievement of high optical properties. Additionally, by simultaneously increasing the orientation of the PVA in advance, problems such as a decrease in orientation or dissolution of the PVA can be prevented when it is immersed in water during subsequent dyeing or stretching processes, thereby enabling the achievement of high optical properties.In addition, when a PVA-based resin layer is immersed in a liquid, the disturbance of the orientation of polyvinyl alcohol molecules and the deterioration of orientation can be suppressed compared to the case where the PVA-based resin layer does not contain halogens. Accordingly, the optical properties of a polarizer obtained by undergoing a treatment process in which the laminate is immersed in a liquid, such as dyeing treatment and underwater stretching treatment, can be improved. Furthermore, optical properties can be improved by shrinking the laminate in the width direction through a drying shrinkage treatment. The obtained resin substrate / polarizer laminate may be used as is (i.e., the resin substrate may be used as a protective layer for the polarizer), or the resin substrate may be peeled off from the resin substrate / polarizer laminate, and any suitable protective layer according to the purpose may be laminated on the peeled surface and used. Details of such a method for manufacturing a polarizer are described, for example, in Japanese Patent Publication No. 2012-73580 and Japanese Patent No. 6470455. The entire contents of these publications are incorporated herein by reference.
[0044] The polarizer (21) is preferably composed of two or more layers of laminated material, and more preferably may be composed of a laminate of a resin substrate and a PVA-based resin layer applied and formed on the resin substrate.
[0045] The thickness of the polarizer (21) is preferably 15 μm or less, more preferably 12 μm or less, even more preferably 10 μm or less, particularly preferably 8 μm or less, and typically 1 μm or more, preferably 3 μm or more. If the thickness of the polarizer is within this range, the occurrence of warping of the optical laminate under high humidity environments can be suppressed more stably.
[0046] The polarizer (21) preferably exhibits absorption dichroism at any one of the wavelengths 380 nm to 780 nm. The single transmittance of the polarizer (21) is, for example, 41.5% to 46.0%, preferably 43.0% to 46.0%, and more preferably 44.5% to 46.0%. The polarization degree of the polarizer (21) is preferably 97.0% or higher, more preferably 99.0% or higher, and even more preferably 99.9% or higher.
[0047] B-2. Protective layer
[0048] The protective layer (22) is formed from any suitable film that can be used as a protective layer for the polarizer (21). Specific examples of materials that serve as the main component of the film include cellulose-based resins such as triacetylcellulose (TAC), or transparent resins such as polyester-based, polyvinyl alcohol-based, polycarbonate-based, polyamide-based, polyimide-based, polyethersulfone-based, polysulfone-based, polystyrene-based, polynorbornene-based, polyolefin-based, (meth)acrylic-based, and acetate-based resins. Additionally, thermosetting resins or UV-curing resins such as (meth)acrylic-based, urethane-based, (meth)acrylurethane-based, epoxy-based, and silicone-based resins may also be used. Furthermore, "(meth)acrylic-based resin" refers to acrylic-based resins and / or methacrylic-based resins. In addition, glass-based polymers such as siloxane-based polymers may also be used. In addition, a polymer film described in Japanese Patent Publication No. 2001-343529 (WO01 / 37007) may also be used. As a material for this film, for example, a resin composition containing a thermoplastic resin having substituted or unsubstituted imide groups in a side chain and a thermoplastic resin having substituted or unsubstituted phenyl groups and nitrile groups in a side chain may be used, and for example, a resin composition having an alternating copolymer of isobutene and N-methylmaleimide and an acrylonitrile-styrene copolymer may be used. The polymer film may, for example, be an extruded product of the resin composition.
[0049] In one embodiment of the present invention, the protective layer (22) comprises a (meth)acrylic resin. As the (meth)acrylic resin, for example, a (meth)acrylic resin having a glutarimide structure is used. (Meta)acrylic resins having a glutarimide structure are described, for example, in Japanese Patent Publication No. 2006-309033, Japanese Patent Publication No. 2006-317560, Japanese Patent Publication No. 2006-328329, Japanese Patent Publication No. 2006-328334, Japanese Patent Publication No. 2006-337491, Japanese Patent Publication No. 2006-337492, Japanese Patent Publication No. 2006-337493, Japanese Patent Publication No. 2006-337569, Japanese Patent Publication No. 2007-009182, Japanese Patent Publication No. 2009-161744, and Japanese Patent Publication No. 2010-284840. These descriptions are incorporated herein by reference.
[0050] The thickness of the protective layer (22) is typically 300 μm or less, preferably 100 μm or less, more preferably 5 μm to 80 μm, and even more preferably 10 μm to 60 μm. In addition, if surface treatment is performed, the thickness of the protective layer (22) is the thickness including the thickness of the surface treatment layer.
[0051] C. First optical functional body
[0052] The first optical functional body (3) can impart a desired optical function to the optical laminate (1). Examples of the first optical functional body (3) include an anti-reflection laminate, a sunglasses countermeasure laminate, etc.
[0053] The thickness of the first optical functional body (3) is typically 20㎛ to 60㎛, and preferably 30㎛ to 50㎛.
[0054] In one embodiment of the present invention, the first optical functional body (3) is a non-transparency laminate (3a). The non-transparency laminate (3a) includes a non-transparency layer (32) and a first substrate (31) disposed on the visible side of the non-transparency layer (32). The non-transparency layer (32) is supported by the first substrate (31). The non-transparency layer (32) is disposed on the visible side with respect to the protective layer (22) and is bonded to the protective layer (22) through a first adhesive layer (61). The non-transparency layer (32) is in contact with the first adhesive layer (61) and is pressure-bonded to the first adhesive layer (61). The first substrate (31) is located on the opposite side of the first adhesive layer (61) with respect to the non-transparency layer (32). The first substrate (31) is in contact with the second adhesive layer (62) and is pressure-bonded to the second adhesive layer (62).
[0055] C-1. Anti-see-through layer
[0056] The anti-see-through layer (32) is formed to prevent see-through of the user's face, the keyboard of the image display device, external light (e.g., fluorescent lamp), etc. In one embodiment of the present invention, the anti-see-through layer (32) is an orientation solidification layer of a liquid crystal compound. In this specification, "orientation solidification layer" refers to a layer in which a liquid crystal compound is oriented in a predetermined direction within the layer and the orientation state is fixed. Furthermore, "orientation solidification layer" is a concept that includes an orientation cured layer obtained by curing a liquid crystal monomer. The liquid crystal compound may be a rod-shaped liquid crystal compound, a disc-shaped liquid crystal compound, or a combination thereof.
[0057] In one embodiment of the present invention, the anti-see-through layer (32) comprises a discotic liquid crystal compound. More specifically, the anti-see-through layer (32) is a layer in which the discotic liquid crystal compound is immobilized in a state oriented in a predetermined direction. A discotic liquid crystal compound generally refers to a liquid crystal compound having a disc-shaped molecular structure in which a cyclic core, such as benzene, 1,3,5-triazine, or calixarene, is placed at the center of the molecule, and straight-chain alkyl groups, alkoxy groups, or substituted benzoyloxy groups are substituted radially as side chains. Representative examples of discotic liquid crystals include benzene derivatives, triphenylene derivatives, truxene derivatives, and phthalocyanine derivatives described in the research report by C. Destrade's team, Mol. Cryst. Liq. Cryst. Vol. 71, p. 111 (1981), or the research report by B. Kohne's team, Angew. Chem. Examples include cyclohexane derivatives described in Vol. 96, p. 70 (1984), and azacrown-based or phenylacetylene-based macrocycles described in the research report of J. M. Lehn's team, J. Chem. Soc. Chem. Commun., p. 1794 (1985), and the research report of J. Zhang's team, J. Am. Chem. Soc., Vol. 116, p. 2655 (1994). As other specific examples of discotic liquid crystal compounds, examples include compounds described in Japanese Patent Publication No. 2006-133652, Japanese Patent Publication No. 2007-108732, Japanese Patent Publication No. 2010-244038, and Japanese Patent Publication No. 2014-214177. The descriptions in the above documents and publications are incorporated herein by reference. The anti-see-through layer containing a discotic liquid crystal compound can be, for example, a so-called negative A plate having a refractive index characteristic of nx=nz>ny.
[0058] In another embodiment, the anti-see-through layer (32) comprises a rod-shaped liquid crystal compound. More specifically, the anti-see-through layer is oriented such that the rod-shaped liquid crystal compound is arranged in a predetermined direction (typically, the direction of the ground axis) (homogeneous orientation). As a rod-shaped liquid crystal compound, for example, a liquid crystal compound in which the liquid crystal phase is a nematic phase (nematic liquid crystal) may be used. As such a liquid crystal compound, for example, a liquid crystal polymer or a liquid crystal monomer may be used. The mechanism of liquid crystallization of the liquid crystal compound may be either lyotropic or thermotropic. The liquid crystal polymer and the liquid crystal monomer may each be used individually or in combination. Any suitable liquid crystal monomer may be employed as the liquid crystal monomer. For example, polymerizable mesogen compounds described in Japanese Patent Publication No. 2002-533742 (WO00 / 37585), EP358208 (US5211877), EP66137 (US4388453), WO93 / 22397, EP0261712, DE19504224, DE4408171, and GB2280445, etc. may be used. Specific examples of such polymerizable mesogen compounds include, for example, BASF’s trade name LC242, Merck’s trade name E7, and Walker-Chem’s trade name LC-Sillicon-CC3767. As for the liquid crystal monomer, for example, a nematic liquid crystal monomer is preferred. Specific examples of liquid crystal compounds are described, for example, in Japanese Patent Publication No. 2006-163343. The description in the said publication is incorporated herein by reference. A non-see-through layer comprising a rod-shaped liquid crystal compound may, for example, be a so-called positive A plate having a refractive index characteristic of nx > ny = nz.
[0059] The anti-see-through layer (32) can function as a λ / 2 plate. When the anti-see-through layer (32) functions as a λ / 2 plate, see-through can be effectively prevented by controlling its orientation angle (or ground axis direction). The in-plane phase difference Re (550) of the anti-see-through layer (32) is 220 nm to 320 nm, more preferably 240 nm to 300 nm, and even more preferably 250 nm to 280 nm.
[0060] The angle formed by the ground axis of the anti-see-through layer (32) and the absorption axis of the polarizer (21) is preferably 35° to 55°, more preferably 40° to 50°, and even more preferably about 45°. By arranging the anti-see-through layer (32), which functions as a λ / 2 plate, at these axial angles, see-through can be effectively prevented.
[0061] The thickness of the see-through prevention layer (32) is preferably 1 μm to 5 μm, and more preferably 1 μm to 3 μm.
[0062] When an alignment layer is used for the alignment of a liquid crystal compound, the anti-see-through laminate (3a) further comprises an alignment layer between the anti-see-through layer (32) and the first substrate (31). That is, the anti-see-through laminate (3a) may be composed of the anti-see-through layer (32), the alignment layer, and the first substrate (31). The alignment layer generally includes a polymer material as a main component. Representative examples of polymer materials include polyvinyl alcohol, polyimide, and derivatives thereof. In one embodiment of the present invention, modified or unmodified polyvinyl alcohol is preferred. As an alignment layer, for example, modified polyvinyl alcohol described in W01 / 88574A1 and Japanese Patent No. 3907735 may be used. An alignment treatment is typically performed on the alignment layer. Representative examples of alignment treatments include rubbing treatment and photo-alignment treatment. Since rubbing treatment is well known in the industry, a detailed description is omitted. As for the photo-aligned alignment film (photo-aligned film), for example, the one described in WO2005 / 096041, the product name LPP-JP265CP manufactured by Rolic Technologies, etc., may be used. The thickness of the alignment film is, for example, 0.01 μm to 10 μm, preferably 0.01 μm to 1 μm, and more preferably 0.01 μm to 0.5 μm.
[0063] The anti-see-through layer (32) can be formed, for example, in the following steps. First, a coating solution for forming an alignment layer is applied to the first substrate (31) and dried to form a coating film. A rubbing treatment is performed on the coating film in a predetermined direction, and an alignment layer is formed on the first substrate (31). The predetermined direction may correspond to the ground axis direction of the obtained anti-see-through layer (32). Next, a coating solution for forming an anti-see-through layer (for example, a solution containing a liquid crystal compound and, if necessary, a crosslinkable monomer) is applied to the formed alignment film and heated. By heating, the solvent of the coating solution is removed, and the alignment of the liquid crystal compound is carried out. Heating may be performed in a single step, or in multiple steps with varying temperatures. Next, the crosslinkable (or polymerizable) monomer is crosslinked (or polymerized) by ultraviolet irradiation to fix the alignment of the liquid crystal compound. In this way, a non-transparent layer (32) is formed on the first substrate (31) (substantially, on the alignment layer). Also, a method for aligning a discotic liquid crystal compound is described, for example, in Japanese Patent Publication No. 2014-214177, and a method for aligning a rod-shaped liquid crystal compound is described, for example, in Japanese Patent Publication No. 2006-163343. The descriptions in these publications are incorporated herein by reference. Also, the alignment layer may be omitted depending on the desired alignment state and the type of liquid crystal compound.
[0064] C-2. First entry
[0065] The first material (31) is used to form a see-through prevention layer (32).
[0066] As the first substrate (31), any suitable resin film is used. Examples of materials for forming the resin film include polyester resins such as polyethylene terephthalate (PET), cycloolefin resins such as norbornene resins, resins obtained by addition polymerization of cycloolefin (e.g., norbornene) and α-olefin (e.g., ethylene) (COC), and cellulose resins such as triacetylcellulose (TAC). In one embodiment of the present invention, the first substrate (31) comprises a TAC-based resin.
[0067] The thickness of the first substrate (31) can be appropriately set according to the purpose. The thickness of the first substrate (31) is typically 20㎛ to 200㎛, preferably 25㎛ to 100㎛, and more preferably 30㎛ to 50㎛.
[0068] D. Reinforcement layer
[0069] The reinforcing layer (5) imparts excellent resistance to localized loads to the optical laminate (1). In one embodiment of the present invention, the reinforcing layer (5) is bonded to the first substrate (31) through a second adhesive layer (62). The reinforcing layer (5) is positioned between the second adhesive layer (62) and the third adhesive layer (63). The reinforcing layer (5) is in contact with the second adhesive layer (62) and the third adhesive layer (63) and is pressure-bonded to the second adhesive layer (62) and the third adhesive layer (63).
[0070] The reinforcing layer (5) is formed from any suitable film. As specific examples of the material that is the main component of the reinforcing layer (5), examples include the same material as the main component of the protective layer (22) described in claim B-2 above (the transparent resin, the thermosetting resin or UV-curing resin, the glassy polymer, and the resin composition). In one embodiment of the present invention, the reinforcing layer (5) comprises a (meth)acrylic resin, preferably a (meth)acrylic resin having a glutarimide structure. That is, each of the protective layer (22) and the reinforcing layer (5) comprises a (meth)acrylic resin. By using a (meth)acrylic resin as the protective layer (22) and the reinforcing layer (5), light leakage can be stably suppressed when a load greater than a predetermined value is locally applied to the optical laminate (1).
[0071] In addition, the reinforcing layer (5), like the protective layer (22), may be subjected to the surface treatment described above and / or the treatment to improve visibility described above as necessary.
[0072] The thickness of the reinforcing layer (5) is typically 20㎛ to 70㎛, and preferably 30㎛ to 50㎛. If the thickness of the reinforcing layer (5) is within this range, excellent resistance to localized loads can be imparted to the optical laminate (1), and at the same time, bending of the optical laminate (1) under high humidity environments can be sufficiently suppressed.
[0073] E. Second optical functional body
[0074] The second optical functional body (4) can impart an optical function to the optical laminate (1) that is different from the first optical functional body (3). Examples of the second optical functional body (4) include an anti-reflection laminate, a sunglasses countermeasure laminate, etc.
[0075] The thickness of the second optical functional body (4) is typically 40㎛ to 120㎛, and preferably 70㎛ to 100㎛ or less.
[0076] In one embodiment of the present invention, the second optical functional body (4) is an anti-reflection laminate (4a). The anti-reflection laminate (4a) includes a second substrate (41), a hard coat layer (42) disposed on the visible side of the second substrate (41), and an anti-reflection layer (43) disposed on the visible side of the hard coat layer (42). That is, the anti-reflection laminate (4a) may be composed of a second substrate (41), a hard coat layer (42), and an anti-reflection layer (43). The second substrate (41) is disposed on the visible side with respect to the reinforcing layer (5) and is bonded to the reinforcing layer (5) through a third adhesive layer (63). The second substrate (41) is in contact with the third adhesive layer (63) and is pressure-bonded to the third adhesive layer (63). In one embodiment of the present invention, the hard coat layer (42) is formed directly on the visible side surface of the second substrate (41). In this specification, "directly" means that no adhesive layer or adhesive layer is interposed. Additionally, the anti-reflection layer (43) is formed directly on the visible side surface of the hard coat layer (42).
[0077] E-1. Entry No. 2
[0078] The second substrate (41) is used to form a hard coat layer (42) and an anti-reflective layer (43). Any suitable resin film is used as the second substrate (41). As the forming material of the second substrate (41), examples include the same as the forming material of the first substrate (31) described in claim C-2 above (the polyester resin, the cycloolefin resin, the resin obtained by the addition polymerization of the cycloolefin and α-olefin, and the cellulose resin). In one embodiment of the present invention, the second substrate (41) comprises a TAC resin.
[0079] The thickness of the second substrate (41) can be appropriately set according to the purpose. The thickness of the second substrate (41) is typically 20㎛ to 200㎛, preferably 50㎛ to 150㎛, and more preferably 70㎛ to 90㎛.
[0080] E-2. Hard Coat Layer
[0081] The hard coat layer (42) can impart excellent pencil hardness to the optical laminate (1). Additionally, by appropriately adjusting the difference in refractive index between the hard coat layer (42) and the anti-reflection layer (43), the reflectivity of the optical laminate (1) can be further reduced.
[0082] The hard coat layer (42) preferably has sufficient surface hardness, excellent mechanical strength, and excellent light transmittance. The hard coat layer (42) can be formed from any suitable resin as long as it has these desired characteristics. Specific examples of resins include thermosetting resins, thermoplastic resins, UV-curing resins, electron beam-curing resins, and two-component mixed resins. Among the resins forming the hard coat layer (42), UV-curing resins are preferred. If the resin is a UV-curing resin, the hard coat layer (42) can be formed with simple operation and high efficiency.
[0083] Specific examples of UV-curing resins include polyester-based, acrylic-based, urethane-based, amide-based, silicone-based, and epoxy-based UV-curing resins. UV-curing resins include UV-curing monomers, oligomers, and polymers. Preferred UV-curing resins include resin compositions comprising acrylic-based monomer or oligomer components having preferably two or more, more preferably three to six, UV-polymerizable functional groups. Representatively, a photopolymerization initiator is incorporated into the UV-curing resin.
[0084] The hard coat layer (42) can be formed by any suitable method. For example, the hard coat layer (42) can be formed by coating a resin composition for forming a hard coat layer onto a second substrate (41), drying it, and then curing the dried coating film by irradiating it with ultraviolet rays.
[0085] The thickness of the hard coat layer (42) is, for example, 0.5㎛ to 20㎛, preferably 1㎛ to 15㎛.
[0086] Details regarding the hard coat layer and the adhesion structure between the hard coat layer and the anti-reflective layer are described, for example, in Japanese Patent Publication No. 2016-224443. The description in the above publication is incorporated herein by reference.
[0087] E-3. Anti-reflective layer
[0088] The anti-reflection layer (43) is formed to prevent reflection of external light (e.g., fluorescent lamp). Any suitable configuration may be adopted as the composition of the anti-reflection layer (43). Representative configurations of the anti-reflection layer (43) include: (1) a single layer of a low refractive index layer with an optical film thickness of 120 nm to 140 nm and a refractive index of 1.35 to 1.55; (2) a laminate having a medium refractive index layer, a high refractive index layer, and a low refractive index layer in order from the second substrate (41); and (3) an alternating multilayer laminate of a high refractive index layer and a low refractive index layer.
[0089] Examples of materials capable of forming a low refractive index layer include silicon oxide (SiO2) and magnesium fluoride (MgF2). The refractive index of the low refractive index layer is typically 1.35 to 1.55. Examples of materials capable of forming a high refractive index layer include titanium oxide (TiO2), niobium oxide (Nb2O3 or Nb2O5), tin-doped indium oxide (ITO), antimony-doped tin oxide (ATO), and ZrO2-TiO2. The refractive index of the high refractive index layer is typically 1.60 to 2.20. Examples of materials capable of forming a medium refractive index layer include titanium oxide (TiO2) and a mixture of the material capable of forming a low refractive index layer and the material capable of forming a high refractive index layer (e.g., a mixture of titanium oxide and silicon oxide). The refractive index of the medium refractive index layer is typically about 1.50 to 1.85. The thicknesses of the low refractive index layer, the medium refractive index layer, and the high refractive index layer can be set so that an appropriate optical film thickness is realized according to the layer structure of the anti-reflection layer and the desired anti-reflection performance.
[0090] The anti-reflection layer (43) is typically formed by a dry process. Specific examples of the dry process include the Physical Vapor Deposition (PVD) method and the Chemical Vapor Deposition (CVD) method. Examples of the PVD method include vacuum deposition, reactive deposition, ion beam assist, sputtering, and ion plating. Examples of the CVD method include plasma CVD. The dry process for forming the anti-reflection layer (43) is preferably the sputtering method.
[0091] The thickness of the anti-reflection layer (43) is, for example, about 20 nm to 300 nm.
[0092] The anti-reflection layer (43) preferably has a difference between the maximum reflectance and the minimum reflectance in the wavelength range of 400 nm to 700 nm of 2.0% or less, more preferably 1.9% or less, and even more preferably 1.8% or less. If the difference between the maximum reflectance and the minimum reflectance is within this range, the staining of reflected light can be effectively prevented.
[0093] In one embodiment of the present invention, the anti-reflective layer (43) is located on the outermost surface of the optical laminate (1) on the visible side. The moisture permeability of the anti-reflective layer (43) is typically 1.0 g / mm 2 Below, preferably 0.1 g / mm 2 It is less than or equal to, typically 0.01 g / mm 2 That concludes the report. Additionally, water vapor transmission was measured in accordance with the water vapor transmission test (cup method) of JIS Z0208 for an area of 1 m² in an atmosphere of 40°C and 92%RH humidity. 2 The amount of water vapor (g) passing through the sample in 24 hours can be measured. If the water vapor permeability of the anti-reflective layer (43) located on the outermost surface is below the upper limit, the bending of the optical laminate (1) under high humidity conditions can be suppressed more stably.
[0094] Additionally, the anti-reflection layer (43) does not need to be located on the outermost surface of the optical laminate (1). The anti-reflection laminate (4a) may form an outermost surface layer on the visible side of the anti-reflection layer (43) as needed. That is, the anti-reflection laminate (4a) may be composed of a second substrate (41), a hard coat layer (42), an anti-reflection layer (43), and an outermost surface layer. The range of moisture permeability of the outermost surface layer is the same as the range of moisture permeability of the anti-reflection layer (43) described above. As the outermost surface layer, for example, an anti-fouling layer may be used. The anti-fouling layer may include, for example, a silane-based compound containing a fluorine group (for example, an alkoxysilane compound having a perfluoropolyether group) or an organic compound containing a fluorine group. The anti-fouling layer preferably exhibits water repellency with a water contact angle of 110 degrees or more.
[0095] F. First adhesive layer, second adhesive layer and third adhesive layer
[0096] Each of the first adhesive layer (61), the second adhesive layer (62), and the third adhesive layer (63) is formed from an adhesive (pressure-sensitive adhesive). More specifically, the first adhesive layer (61) is formed by coating the adhesive onto the protective layer (22) of the polarizing plate (2) to the thickness described above. The second adhesive layer (62) is formed by coating the adhesive onto the first substrate (31) of the first optical functional body (3) to the thickness described above. The third adhesive layer (63) is formed by coating the adhesive onto the reinforcing layer (5) to the thickness described above. The first adhesive layer (61), the second adhesive layer (62), and the third adhesive layer (63) may be formed from the same adhesive or from different adhesives. In one embodiment of the present invention, the first adhesive layer (61), the second adhesive layer (62), and the third adhesive layer (63) are formed from the same adhesive. If the first adhesive layer (61), the second adhesive layer (62), and the third adhesive layer (63) are formed from the same adhesive, the manufacturing cost of the optical laminate (1) can be reduced.
[0097] The adhesive typically contains a (meth)acrylic polymer, a urethane polymer, a silicone polymer, or a rubber polymer as a base polymer. When a (meth)acrylic polymer is used as the base polymer, the adhesive layer is formed, for example, with an adhesive containing the (meth)acrylic polymer.
[0098] F-1. (Meta)acrylic polymer
[0099] A (meth)acrylic polymer contains a polymer of a monomer component (raw material monomer) having alkyl (meth)acrylate as the main component. In other words, the (meth)acrylic polymer contains structural units derived from alkyl (meth)acrylate. It is preferable that the alkyl (meth)acrylate constitute 50% by weight or more of the total monomer component serving as the raw material for the (meth)acrylic polymer, and it may be arbitrarily set as the remainder of the monomer other than the alkyl (meth)acrylate. Furthermore, (meth)acrylate refers to acrylate and / or methacrylate.
[0100] Examples of alkyl (meth)acrylates constituting the main backbone of a (meth)acrylic polymer include those having a straight-chain or branched-chain alkyl group with 1 to 18 carbon atoms. Examples of alkyl groups include methyl, ethyl, propyl, isopropyl, butyl, isobutyl, amyl, hexyl, cyclohexyl, heptyl, 2-ethylhexyl, isooctyl, nonyl, decyl, isodecyl, dodecyl, isomyristyl, lauryl, tridecyl, pentadecyl, hexadecyl, heptadecyl, octadecyl, etc. Alkyl (meth)acrylates may be used alone or in combination. It is preferable that the average number of carbon atoms in the alkyl group is 3 to 10.
[0101] (Metha)acrylic polymers may contain structural units derived from copolymer monomers capable of polymerizing with alkyl (meth)acrylates in addition to structural units derived from alkyl (meth)acrylates. That is, the monomer component that serves as a raw material for (meth)acrylic polymers may further include copolymer monomers in addition to alkyl (meth)acrylates.
[0102] Examples of copolymer monomers include carboxyl group-containing monomers, hydroxyl group-containing monomers, amino group-containing monomers, amide group-containing monomers, cyclic polymerizable monomers, epoxy group-containing monomers, sulfonic acid group-containing monomers, phosphate group-containing monomers, polyfunctional acrylates, (meth)acrylic acid esters having alicyclic hydrocarbon groups, (meth)acrylic acid esters having aromatic hydrocarbon groups, vinyl esters, aromatic vinyl compounds, dienes, vinyl ethers, vinyl chloride, etc. Copolymer monomers may be used alone or in combination.
[0103] Among these copolymer monomers, preferably, monomers containing reactive groups capable of reacting with the crosslinking agent described below may be used, and more preferably, monomers containing carboxyl groups or monomers containing hydroxyl groups may be used. Monomers containing reactive groups serve as reaction sites with the crosslinking agent when the adhesive contains the crosslinking agent described below. Since monomers containing carboxyl groups and hydroxyl groups have high reactivity with intermolecular crosslinking agents, they are preferably used to improve the cohesiveness or heat resistance of the resulting adhesive layer. Furthermore, monomers containing carboxyl groups are preferred for achieving both durability and reworkability, and monomers containing hydroxyl groups are preferred for improving reworkability. Copolymer monomers can be used alone or in combination as raw material monomers for (meth)acrylic polymers.
[0104] A carboxyl group-containing monomer is a compound that includes a carboxyl group in its structure and also contains polymerizable unsaturated double bonds such as (meth)acryloyl groups and vinyl groups. Examples of carboxyl group-containing monomers include (meth)acrylic acid, carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, itaconic acid, maleic acid, fumaric acid, and crotonic acid. Among these, acrylic acid is preferred. The (meth)acrylic polymer may preferably contain structural units derived from the carboxyl group-containing monomer, and more preferably structural units derived from (meth)acrylic acid. If the (meth)acrylic polymer contains structural units derived from the carboxyl group-containing monomer, the adhesive properties of the adhesive layer can be improved.
[0105] When a carboxyl group-containing monomer is used as a raw material monomer, the content of the carboxyl group-containing monomer is typically 0.01% by weight or more and 10% by weight or less in the total monomer component that serves as a raw material for the (meth)acrylic polymer.
[0106] Hydroxyl group-containing monomers are compounds that contain hydroxyl groups in their structure and also contain polymerizable unsaturated double bonds such as (meth)acryloyl groups and vinyl groups. Examples of hydroxyl group-containing monomers include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, and 12-hydroxylauryl (meth)acrylate; and (4-hydroxymethylcyclohexyl)-methylacrylate. Among these, 2-hydroxyethyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate are preferred, and 4-hydroxybutyl (meth)acrylate is more preferred. The (meth)acrylic polymer may preferably include structural units derived from hydroxyl group-containing monomers, more preferably structural units derived from 2-hydroxyethyl (meth)acrylate and / or 4-hydroxybutyl (meth)acrylate. If the (meth)acrylic polymer includes structural units derived from hydroxyl group-containing monomers, the durability of the adhesive layer can be improved.
[0107] When a hydroxyl group-containing monomer is used as a raw material monomer, the content of the hydroxyl group-containing monomer is typically 0.01% by weight or more and 10% by weight or less in the total monomer component that serves as a raw material for the (meth)acrylic polymer.
[0108] The weight average molecular weight (Mw) of the (meth)acrylic polymer is, for example, 200,000 to 3 million, preferably 1 million to 2.5 million, and more preferably 1.2 million to 2.5 million. When the weight average molecular weight (Mw) is in this range, an adhesive layer with excellent durability (especially heat resistance) can be obtained. If the weight average molecular weight (Mw) exceeds 3 million, an increase in viscosity and / or gelation during polymer polymerization may occur.
[0109] F-2. Crosslinking agent
[0110] The adhesive may contain a crosslinking agent. As crosslinking agents, organic crosslinking agents, polyfunctional metal chelates, etc. Examples of organic crosslinking agents include isocyanate-based crosslinking agents, peroxide-based crosslinking agents, epoxy-based crosslinking agents, and imine-based crosslinking agents. Polyfunctional metal chelates are formed in which a polyvalent metal is covalently or coordinately bonded to an organic compound. If the adhesive is of the radiation-curable type, polyfunctional monomers may be used as crosslinking agents. Crosslinking agents may be used alone or in combination. Preferably, the crosslinking agents include isocyanate-based crosslinking agents and peroxide-based crosslinking agents.
[0111] When a crosslinking agent is added to the adhesive, the amount of the crosslinking agent is typically 0.01 to 15 parts by weight per 100 parts by weight of the (meth)acrylic polymer (base polymer). When an isocyanate-based crosslinking agent is added to the adhesive, the amount of the isocyanate-based crosslinking agent is typically 0.01 to 15 parts by weight per 100 parts by weight of the (meth)acrylic polymer, preferably 1.0 to 10 parts by weight, and more preferably 2.5 to 5 parts by weight. When a peroxide-based crosslinking agent is added to the adhesive, the amount of the peroxide-based crosslinking agent is typically 0.01 to 2 parts by weight per 100 parts by weight of the (meth)acrylic polymer, preferably 0.1 to 0.5 parts by weight. If the mixing ratio of the crosslinking agent (isocyanate-based crosslinking agent and peroxide-based crosslinking agent) is within the above range, the elastic modulus of the adhesive layer described below can be smoothly adjusted to a desired range when the raw monomer component of the (meth)acrylic polymer contains a monomer containing a reactive group.
[0112] F-3. Silane coupling agents containing reactive functional groups
[0113] The adhesive may contain a silane coupling agent containing a reactive functional group. The reactive functional group of the silane coupling agent containing a reactive functional group is typically a functional group other than an acid anhydride group. Examples of functional groups other than acid anhydrides include epoxy groups, mercapto groups, amino groups, isocyanate groups, isocyanurate groups, vinyl groups, styryl groups, acetacetyl groups, ureido groups, thiourea groups, (meth)acrylic groups, heterocyclic groups, and combinations thereof. The silane coupling agent containing a reactive functional group may be used alone or in combination.
[0114] When a silane coupling agent containing a reactive functional group is incorporated into an adhesive, the amount of the silane coupling agent containing a reactive functional group is typically 0.001 parts by weight or more and 5 parts by weight or less per 100 parts by weight of the (meth)acrylic polymer.
[0115] F-4. Additives
[0116] The adhesive may contain (meth)acrylic oligomers and / or ionic compounds. Additionally, the adhesive may contain additives. Specific examples of additives include powders such as coloring agents and pigments, dyes, surfactants, plasticizers, tackifiers, surface lubricants, leveling agents, softeners, antioxidants, anti-aging agents, light stabilizers, UV absorbers, polymerization inhibitors, inorganic or organic fillers, metal powders, granular materials, and thin materials. Additionally, within a controllable range, a redox system with a reducing agent added may be used. Furthermore, the adhesive may contain a polyether compound having a reactive group (e.g., a reactive silyl group). The type, number, combination, and content of the additives can be appropriately set according to the purpose. The content of the additive is preferably 5 parts by weight or less, more preferably 3 parts by weight or less, and even more preferably 1 part by weight or less, per 100 parts by weight of the (meth)acrylic polymer.
[0117] F-5. Properties of Adhesives
[0118] The storage modulus of the adhesive at 23°C and 55%RH is typically 0.05 GPa or higher, preferably 0.11 GPa or higher, and typically 0.2 GPa or lower, preferably 0.15 GPa or lower. In addition, the storage modulus can be measured in accordance with JIS K 7244 using the dynamic viscoelasticity measuring device "ARES" manufactured by Rheometric. If the elastic modulus of the adhesive is within this range, the resistance of the optical laminate (1) to localized loads can be further improved.
[0119] G. First phase difference layer
[0120] The first phase difference layer (7) may be composed of a phase difference film having any suitable optical properties and / or mechanical properties depending on the purpose. The first phase difference layer (7) is located on the opposite side of the polarizer (2) from the visible side. The first phase difference layer (7) is typically bonded to the opposite side of the polarizer (21) from the visible side through any suitable adhesive layer. The first phase difference layer (7) may also serve as a protective layer on the opposite side of the polarizer (21).
[0121] The thickness of the first phase difference layer (7) is preferably 10㎛ to 60㎛, and more preferably 30㎛ to 50㎛.
[0122] The in-plane phase difference Re (550) of the first phase difference layer (7) is preferably 80 nm to 150 nm, more preferably 90 nm to 140 nm, and even more preferably 100 nm to 130 nm.
[0123] As described above, the first phase difference layer (7) preferably exhibits a refractive index characteristic of nx > ny > nz. The Nz coefficient of the first phase difference layer (7) is preferably 1.1 to 3.0, and more preferably 1.3 to 2.7.
[0124] The first phase difference layer (7) may preferably be positioned such that its ground axis is substantially parallel to the absorption axis of the polarizer (21). In this specification, the expressions “substantially parallel” and “approximately parallel” include cases where the angle between two directions is 0°±7°, preferably 0°±5°, and more preferably 0°±3°. The expressions “substantially orthogonal” and “approximately orthogonal” include cases where the angle between two directions is 90°±7°, preferably 90°±5°, and more preferably 90°±3°. Additionally, in this specification, when simply “orthogonal” or “parallel” is used, it is understood to include a substantially orthogonal or substantially parallel state.
[0125] The first phase difference layer (7) preferably has an absolute value of photoelastic coefficient of 2×10 -11 m 2 / N or less, more preferably 2.0×10 -13 m 2 / N~1.5×10 -11 m 2 / N, more preferably 1.0×10 -12 m 2 / N~1.2×10 -11 m 2 It includes a resin of / N. If the absolute value of the photoelastic modulus is within this range, it is difficult for a phase difference change to occur when shrinkage stress occurs during heating. Therefore, by forming the first phase difference layer (7) using a resin having such an absolute value of the photoelastic modulus, thermal non-uniformity can be effectively prevented when the optical laminate (1) is applied to an image display device.
[0126] The first phase difference layer (7) may exhibit inverse wavelength dispersion characteristics in which the phase difference value increases with the wavelength of the measurement light, or positive wavelength dispersion characteristics in which the phase difference value decreases with the wavelength of the measurement light, or flat wavelength dispersion characteristics in which the phase difference value hardly changes with the wavelength of the measurement light. It is preferable for the first phase difference layer (7) to exhibit flat wavelength dispersion characteristics. Specifically, Re(450) / Re(550) of the first phase difference layer (7) is preferably 0.99 to 1.03, and Re(650) / Re(550) is preferably 0.98 to 1.02. By arranging the λ / 2 plate (first phase difference layer) and the λ / 4 plate (second phase difference layer) having flat wavelength dispersion characteristics at a predetermined axis angle, it is possible to obtain characteristics close to ideal inverse wavelength dispersion characteristics, and as a result, very excellent anti-reflection characteristics can be realized.
[0127] The first phase difference layer (7) may be composed of any suitable resin film capable of satisfying the above characteristics. Representative examples of such resins include cyclic olefin resins, polycarbonate resins, cellulose resins, polyester resins, polyvinyl alcohol resins, polyamide resins, polyimide resins, polyether resins, polystyrene resins, and acrylic resins. Among these, cyclic olefin resins may be suitably used. The first phase difference layer (7) is obtained, for example, by stretching a film formed from the above resin. Details regarding the cyclic olefin resin and the method of stretching the resin film (method of forming the phase difference film) are described, for example, in Japanese Patent Publication No. 2015-210459 and Japanese Patent Publication No. 2016-105166. The descriptions in these publications are incorporated herein by reference.
[0128] H. Second phase difference layer
[0129] The second phase difference layer (8) may be composed of a phase difference film having any suitable optical properties and / or mechanical properties depending on the purpose. The second phase difference layer (8) is located on the opposite side to the visible side of the first phase difference layer (7). The second phase difference layer (8) is typically bonded to the opposite side to the visible side of the first phase difference layer (7) through any suitable adhesive layer.
[0130] The thickness of the second phase difference layer (8) is preferably 10㎛ to 50㎛, and most preferably 20㎛ to 40㎛.
[0131] The in-plane phase difference Re (550) of the second phase difference layer (8) is preferably 10 nm to 60 nm, more preferably 20 nm to 50 nm, and even more preferably 30 nm to 40 nm.
[0132] As described above, the second phase difference layer (8) preferably exhibits a refractive index characteristic of nz > nx > ny. The Nz coefficient of the second phase difference layer (8) is preferably -10 to -0.1, and more preferably -5 to -1.
[0133] The second phase difference layer (8) can preferably be positioned so that its ground axis is substantially orthogonal to the absorption axis of the polarizer (21).
[0134] The second phase difference layer (8) may be composed of any suitable resin film capable of satisfying the above characteristics. Such a resin may, for example, be a polymer having negative intrinsic birefringence. A polymer having negative intrinsic birefringence refers to a polymer in which the refractive index in the orientation direction becomes relatively smaller when the polymer is oriented by stretching or the like. Examples of polymers having negative intrinsic birefringence include those in which chemical bonds or functional groups with large polarization anisotropy, such as aromatic or carbonyl groups, are introduced into the side chains of the polymer. Specific examples include modified polyolefin resins (e.g., modified polyethylene resins), acrylic resins, styrene resins, maleimide resins, fumaric acid ester resins, etc. The second phase difference layer (8) may be obtained, for example, by appropriately stretching a film formed from the above resin.
[0135] Also, in one embodiment of the present invention, the optical laminate (1) has a first phase difference layer (7) and a second phase difference layer (8), but the optical laminate does not have to have a first phase difference layer and / or a second phase difference layer.
[0136] I. Panel-side adhesive layer
[0137] The panel-side adhesive layer (9) is located on the opposite side of the second phase difference layer (8) from the visible side. The panel-side adhesive layer (9) is typically formed by coating any suitable adhesive onto the second phase difference layer (8). The thickness of the panel-side adhesive layer (9) is preferably 1 μm to 60 μm, and more preferably 5 μm to 30 μm. Also, in one embodiment of the present invention, the optical laminate (1) has the panel-side adhesive layer (9), but the optical laminate does not have to have the panel-side adhesive layer.
[0138] J. Image display device
[0139] The optical laminates described in claims A through I above may be applied to an image display device. Accordingly, one embodiment of the present invention includes an image display device using such an optical laminate. Representative examples of image display devices include liquid crystal display devices and organic EL display devices. An image display device according to an embodiment of the present invention typically has the optical laminate described in claims A through I above on its viewing side. The image display device includes an image display panel. The image display panel includes an image display cell. Furthermore, the image display device may be referred to as an optical display device, the image display panel as an optical display panel, and the image display cell as an optical display cell.
[0140] (Example)
[0141] The present invention will be specifically described below by way of examples, but the present invention is not limited by these examples. In addition, the method for measuring each characteristic is as follows.
[0142] (1) Orange peel
[0143] The optical laminates obtained in the examples and comparative examples were cut into 200mm × 300mm pieces to serve as test samples. In the test samples, the absorption axis direction of the polarizer (MD direction) was parallel to the width direction (a direction perpendicular to the length direction) of the test samples. Subsequently, the test samples were bonded to a black acrylic plate using a panel-side adhesive layer. Light was incident using a fluorescent lamp so that the reflection angle was 45° to 70° on the visible side surface of the test samples bonded to the acrylic plate, and the appearance of the test samples (visible side surface) was observed visually. The results were evaluated according to the following criteria.
[0144] A: Inconspicuous texture
[0145] B: Noticeable unevenness
[0146] C: Significantly noticeable unevenness
[0147] (2) Dolja test
[0148] The optical laminates obtained in the examples and comparative examples were cut into 5cm × 5cm pieces to serve as test samples. Subsequently, the test samples were bonded to a glass plate with a thickness of 1.2mm using a panel-side adhesive layer. The test samples bonded to the glass plate were placed on the stage of an indenter CMS tester (manufactured by Instron, product name: 5581) equipped with a spin jig. The radius of curvature R of the tip of the spin jig was 500㎛. Under room temperature (23℃±3℃) conditions, the spin jig was thrust into the test samples on the stage with a load of 9kg. After the spin test, the optical laminate and standard polarizer were visually observed for light leakage when arranged so that the polarizer of the optical laminate and the polarizer of the standard polarizer were in a cross-nicol state, and evaluated according to the following criteria.
[0149] A: No light leakage is confirmed.
[0150] B: Light leakage is confirmed to be significant enough to have a practical impact.
[0151] C: Light leakage is significant to the extent that it is practically unacceptable.
[0152] (3) Bending in high-humidity environments
[0153] The optical laminate obtained in the examples and comparative examples was cut into a size of 200 mm × 300 mm to serve as a viewing-side sample. In the viewing-side sample, the absorption axis direction of the polarizer (MD direction) was parallel to the width direction (a direction perpendicular to the length direction) of the viewing-side sample. Subsequently, the viewing-side sample was bonded to the surface of a glass plate using a panel-side adhesive layer. The glass plate had a size of 210 mm × 310 mm, and the thickness of the glass plate was 550 μm. Additionally, the laminate obtained in the manufacturing example was cut into a size of 200 mm × 300 mm to serve as a light source-side sample. In the light source-side sample, the absorption axis direction of the polarizer (MD direction) was parallel to the length direction of the light source-side sample. Subsequently, the light source-side sample was bonded to the back surface of the glass plate using an adhesive layer. Accordingly, a test sample was obtained in which the viewing-side sample, the glass plate, and the light source-side sample were laminated.
[0154] Next, the test sample was autoclaved for 15 minutes under normal conditions (50℃, 5 atm), then left to stand for 48 hours under conditions of 23℃ and 55% RH, and subsequently left to stand for 48 hours under conditions of 65℃ and 90% RH. Afterward, the morphology of the test sample was observed visually and evaluated according to the following criteria.
[0155] A: When observing the shape with the backlight-side polarizer (light source-side sample) facing downward, it has a concave shape.
[0156] B: When observing the shape with the backlight-side polarizer (light source-side sample) facing downward, it has a convex shape.
[0157] In addition, if the test sample is convex after the high humidity test, it is interpreted that the upper viewing-side sample (optical laminate of the example and comparative example) is expanded more than the lower light source-side sample (laminated sample of the manufacturing example), and that warping occurs in the viewing-side sample.
[0158] Meanwhile, if the test sample after the high humidity test has a concave shape, it is interpreted that under a high humidity environment, the lower light source-side sample (laminated body of the manufacturing example) expands more than the upper viewing-side sample (optical laminate of the example and comparative example), and the bending of the viewing-side sample is suppressed.
[0159] [Preparation Example 1]
[0160] A polarizing plate was obtained in the same manner as described in “1. Fabrication of a polarizing plate (polarizer laminate)” below. In addition, an acrylic adhesive (adhesive PSA2 described below) was coated on the side opposite to the protective layer in the polarizer to form an adhesive layer. The thickness of the adhesive layer was 20 μm.
[0161] In addition, a reflective polarizer film manufactured by 3M (product name: APF-T35, thickness: 38 μm) was bonded to the side opposite to the polarizer in the protective layer (acrylic resin film) using an acrylic adhesive (adhesive PSA3 described later). Accordingly, an adhesive layer was formed between the acrylic resin film and the reflective polarizer film. The thickness of the adhesive layer was 12 μm.
[0162] According to the above, a laminate having a composition of an adhesive layer / polarizing plate / adhesive layer / reflective polarizer film was obtained.
[0163] <Preparation of Adhesive PSA2>
[0164] 99 parts of butyl acrylate, 1.0 parts of 4-hydroxybutyl acrylate, and 0.3 parts of 2,2'-azobisisobutyronitrile were added together with ethyl acetate to a reaction vessel equipped with a cooling tube, a nitrogen inlet tube, a thermometer, and a stirring device, and reacted at 60°C for 4 hours under a nitrogen gas stream, after which ethyl acetate was added to the reaction solution to obtain a solution (solid content concentration 30 wt%) containing an acrylic polymer A2 with a weight average molecular weight of 1.65 million.
[0165] Acrylic adhesive PSA2 was obtained by combining 0.3 parts of dibenzoyl peroxide (Nippon Chemical Co., Ltd.: Naiper BMT), 0.1 parts of trimethylolpropanexylene diisocyanate (Mitsui Takeda Chemical Co., Ltd.: Takenate D110N), and 0.2 parts of a silane coupling agent (Soken Kagaku Co., Ltd.: A-100, acetacetyl group containing silane coupling agent) with respect to 100 parts of the solid content of the obtained acrylic polymer A2 solution.
[0166] <Preparation of Adhesive PSA3>
[0167] 100 parts of butyl acrylate, 5 parts of acrylic acid, 0.1 parts of 2-hydroxyethyl acrylate, and 0.1 parts of 2,2'-azobisisobutyronitrile as a polymerization initiator were added to a 4-neck flask equipped with a stirring blade, thermometer, nitrogen gas inlet tube, and condenser, along with 100 g of ethyl acetate. After introducing nitrogen gas to purge the mixture while stirring gently, the liquid temperature inside the flask was maintained at around 55°C and a polymerization reaction was carried out for 8 hours to obtain a solution containing an acrylic polymer A3 with a weight average molecular weight of 2.2 million.
[0168] 0.60 parts of an isocyanate crosslinking agent (Coronate L, manufactured by Tosho Co., Ltd.) and 0.20 parts of a silane coupling agent (KBM403, manufactured by Shin-Etsu Kagaku Kogyo Co., Ltd.) were mixed with 100 parts of the solid content of the obtained acrylic polymer A3 solution to obtain an acrylic adhesive PSA3, which is a solution of an acrylic adhesive composition (solid content 11 wt%).
[0169] [Examples 1–3]
[0170] 1. Fabrication of polarizers (polarizer laminates)
[0171] As a thermoplastic resin substrate, an amorphous isophthal copolymer polyethylene terephthalate film (thickness: 100 μm) having a long shape and a Tg of about 75°C was used, and corona treatment was performed on one side of the resin substrate.
[0172] A PVA aqueous solution (coating solution) was prepared by adding 13 parts by weight of potassium iodide to 100 parts by weight of a PVA-based resin mixed in a 9:1 ratio of polyvinyl alcohol (degree of polymerization 4200, degree of saponification 99.2 mol%) and acetacetyl-modified PVA (manufactured by Nippon Kosei Kagaku Kogyo Co., Ltd., trade name "Gosepamer") and dissolving it in water.
[0173] By applying the above PVA aqueous solution to the corona-treated surface of the resin substrate and drying it at 60°C, a PVA-based resin layer with a thickness of 13 μm was formed and a laminate was produced.
[0174] The obtained laminate was uniaxially stretched 2.4 times in the longitudinal direction (length direction) in an oven at 130°C (air-assisted stretching treatment).
[0175] Next, the laminate was immersed for 30 seconds in an insolubilization bath at a liquid temperature of 40°C (an aqueous boric acid solution obtained by mixing 4 parts by weight of boric acid with 100 parts by weight of water) (insolubilization treatment).
[0176] Next, the polarizer was immersed for 60 seconds in a dyeing bath at a liquid temperature of 30°C (an aqueous iodine solution obtained by mixing iodine and potassium iodide in a weight ratio of 1:7 with 100 parts by weight of water) while adjusting the concentration so that the final obtained elemental transmittance (Ts) of the polarizer became a desired value (dyeing treatment).
[0177] Next, it was immersed for 30 seconds in a crosslinking bath at a liquid temperature of 40°C (an aqueous boric acid solution obtained by mixing 3 parts by weight of potassium iodide and 5 parts by weight of boric acid with 100 parts by weight of water) (crosslinking treatment).
[0178] Afterwards, the laminate was immersed in an aqueous boric acid solution (boric acid concentration 4 wt%, potassium iodide concentration 5 wt%) at a liquid temperature of 70°C, and uniaxial stretching was performed in the longitudinal direction (length direction) between rolls of different peripheral speeds so that the total stretching ratio was 5.5 times (underwater stretching treatment).
[0179] Afterwards, the laminate was immersed in a cleaning bath at a liquid temperature of 20°C (an aqueous solution obtained by mixing 4 parts by weight of potassium iodide with 100 parts by weight of water) (cleaning treatment).
[0180] Afterwards, while drying in an oven maintained at approximately 90°C, it was brought into contact with a heated SUS roll maintained at a surface temperature of approximately 75°C (drying shrinkage treatment).
[0181] In this way, a polarizer with a thickness of about 5 μm was formed on a resin substrate.
[0182] An acrylic resin film (thickness: 40 μm) having a glutarimide structure was bonded as a protective layer to the surface of the obtained polarizer (the side opposite to the resin substrate) using a UV-curing adhesive. Specifically, the adhesive was coated to a total thickness of approximately 2.0 μm and bonded using a roller machine. Subsequently, UV light was irradiated from the side of the acrylic resin film to cure the adhesive. Then, the resin substrate was peeled off to obtain a polarizing plate having the composition of an acrylic resin film (protective layer) and a polarizer.
[0183] 2. Anti-see-through laminate
[0184] As an anti-see-through laminate, a TAC film with a phase difference layer manufactured by Fujifilm Co., Ltd. (Product name: HL214, thickness: 42㎛) was used.
[0185] 3. Fabrication of Anti-Reflective Laminate
[0186] As an anti-reflective laminate, an AR film manufactured by Dexerials Co., Ltd. (AR + HC thickness 4㎛, substrate thickness: 80㎛) was used.
[0187] 4. Preparation of adhesive
[0188] 4-1. Preparation of Adhesive PSA1 used in the first to third adhesive layers and the panel-side adhesive layer
[0189] A monomer mixture containing 94.9 parts butyl acrylate, 0.1 parts 4-hydroxybutyl acrylate, and 5.0 parts acrylic acid was added to a 4-neck flask equipped with a stirring blade, a thermometer, a nitrogen gas inlet tube, and a condenser. Additionally, 0.1 parts 2,2'-azobisisobutyronitrile was added as a polymerization initiator to 100 parts of this monomer mixture along with 100 parts ethyl acetate. After introducing nitrogen gas to purify the atmosphere while stirring gently, the liquid temperature inside the flask was maintained at around 55°C and the polymerization reaction was carried out for 8 hours to prepare a solution of acrylic polymer A1 with a weight average molecular weight (Mw) of 2.2 million and Mw / Mn=3.0.
[0190] Adhesive PSA1 was obtained by mixing 3 parts of a trimethylolpropane / tolylene diisocyanate adduct (Tosho Co., Ltd., trade name "Coronate L"), 0.2 parts of a peroxide crosslinking agent (benzoyl peroxide), 0.075 parts of an epoxy group-containing silane coupling agent (Shin-Etsu Kagaku Kogyo Co., Ltd., trade name "KBM-403"), and 0.5 parts of a polyether compound having reactive silyl groups (Kaneka Co., Ltd., trade name "Silyl SAT10") with respect to 100 parts of the solid content of an acrylic polymer A1 solution. The storage modulus of the adhesive constituting the adhesive layer was measured in accordance with JIS K 7244 using a dynamic viscoelasticity measuring device "ARES" manufactured by Rheometric Co., Ltd. The storage modulus of adhesive PSA1 at 23°C and 55%RH was 0.11 GPa.
[0191] 5. Fabrication of Optical Laminates
[0192] An anti-transparency laminate was bonded onto the protective layer of a polarizing plate using adhesive PSA1. Specifically, adhesive PSA1 was applied to the visible side surface of the protective layer to form a first adhesive layer having the thickness shown in Table 1, and then the anti-transparency layer of the anti-transparency laminate was brought into contact with the first adhesive layer to bond the anti-transparency laminate to the polarizing plate through the first adhesive layer. At this time, the ground axis of the anti-transparency layer (the orientation solidification layer of the liquid crystal compound) was adjusted to form an angle of 45° with respect to the absorption axis of the polarizer.
[0193] Next, an acrylic resin film (thickness: 40 μm) having a glutarimide structure as a reinforcing layer was bonded onto the first substrate of the anti-see-through laminate through adhesive PSA1. Specifically, adhesive PSA1 was applied to the visible side surface of the first substrate to form a second adhesive layer having the thickness shown in Table 1, and the reinforcing layer was brought into contact with the second adhesive layer and bonded to the anti-see-through laminate.
[0194] Next, an anti-reflective laminate was bonded onto a reinforcing layer using adhesive PSA1. Specifically, adhesive PSA1 was applied to the visible side surface of the reinforcing layer to form a third adhesive layer having the thickness shown in Table 1, and then a second substrate of the anti-reflective laminate was brought into contact with the second adhesive layer to bond the anti-reflective laminate to the reinforcing layer through the third adhesive layer.
[0195] In addition, a cyclic olefin film (refractive index characteristics: nx > ny > nz, in-plane phase difference: 116 nm) as a first phase difference layer was bonded to the side opposite to the protective layer in the polarizer using a UV-curing adhesive. At this time, the ground axis of the first phase difference layer was adjusted to form an angle of 0° with respect to the absorption axis of the polarizer. Subsequently, a modified polyethylene film (refractive index characteristics: nz > nx > ny, in-plane phase difference: 35 nm) as a second phase difference layer was bonded to the side opposite to the polarizer in the first phase difference layer using a UV-curing adhesive. At this time, the ground axis of the second phase difference layer was adjusted to form an angle of 90° with respect to the absorption axis of the polarizer.
[0196] Next, adhesive PSA1 was applied to the side opposite to the first phase difference layer in the second phase difference layer to form a panel-side adhesive layer having the thickness shown in Table 1.
[0197] Based on the above, an optical laminate was obtained having a composition of an anti-reflective laminate / a third adhesive layer / a reinforcing layer / a second adhesive layer / an anti-transparency laminate / a first adhesive layer / a polarizer / a first phase difference layer / a second phase difference layer / a panel-side adhesive layer. Table 1 shows the thickness of each layer of the optical laminate, the total thickness of the optical laminate, and the total thickness of the anti-transparency laminate, the reinforcing layer, and the anti-reflective laminate. In addition, the optical laminate was subjected to the evaluation of the orange peel, spin test (light leakage), and bending under high humidity conditions. The results, along with the total thickness of the anti-transparency laminate, the reinforcing layer, and the anti-reflective laminate, and the thickness of each adhesive layer, are shown in Table 2.
[0198] [Comparative Example 1]
[0199] An optical laminate having the configuration of a first adhesive layer / polarizing plate / first phase difference layer / second phase difference layer / panel-side adhesive layer was obtained by making it the same as Example 2, except that only the first adhesive layer was formed on the viewing side rather than the polarizing plate, and the thickness of the panel-side adhesive layer was changed to the value shown in Table 1.
[0200] [Comparative Example 2]
[0201] An optical laminate having the configuration of a first adhesive layer and a first adhesive layer and a second adhesive layer on the viewing side rather than the polarizer, in the same manner as Comparative Example 1 except that only the first adhesive layer and the first adhesive layer were formed on the viewing side rather than the polarizer, was obtained.
[0202] [Comparative Example 3]
[0203] An optical laminate having the configuration of an anti-reflection laminate / second adhesive layer / anti-reflection laminate / first adhesive layer / polarizing plate / first phase difference layer / second phase difference layer / panel-side adhesive layer was obtained by performing the same procedure as Comparative Example 1, except that a reinforcing layer was not formed between the anti-reflection laminate and the anti-reflection laminate, and the anti-reflection laminate was bonded to the anti-reflection laminate through the second adhesive layer.
[0204] [Comparative Example 4]
[0205] An optical laminate having the configuration of an anti-reflection laminate / second adhesive layer / anti-transparency laminate / first adhesive layer / polarizing plate / first phase difference layer / second phase difference layer / panel-side adhesive layer was obtained by making it the same as Comparative Example 3, except that the thicknesses of the first adhesive layer, the second adhesive layer, the third adhesive layer, and the panel-side adhesive layer were changed to the values shown in Table 1.
[0206] [Comparative Example 5]
[0207] An optical laminate having the configuration of an anti-reflection laminate / a fourth adhesive layer / a second reinforcing layer / a third adhesive layer / a reinforcing layer / a second adhesive layer / an anti-reflection laminate / a first adhesive layer / a polarizing plate / a first phase difference layer / a second phase difference layer / a panel-side adhesive layer was obtained by performing the same procedure as in Example 2, except that a second reinforcing layer and a fourth adhesive layer were formed between the third adhesive layer and the anti-reflection laminate, and the thickness of the panel-side adhesive layer was changed to the value shown in Table 1. In addition, the second reinforcing layer was an acrylic resin film having a glutarimide structure (thickness: 40 μm). In addition, the fourth adhesive layer was formed by coating the visible side surface of the second reinforcing layer with adhesive PSA1 to the thickness shown in Table 1.
[0208] [Comparative Example 6]
[0209] An optical laminate having the configuration of an anti-reflection laminate / third adhesive layer / reinforcement layer / second adhesive layer / anti-transparency laminate / first adhesive layer / polarizing plate / first phase difference layer / second phase difference layer / panel-side adhesive layer was obtained by performing the same procedure as in Example 2, except that the thickness of the reinforcing layer was changed to 80 μm and the thickness of the panel-side adhesive layer was changed to the value shown in Table 1.
[0210] [Comparative Example 7]
[0211] An optical laminate having the configuration of an anti-reflection laminate / third adhesive layer / reinforcement layer / second adhesive layer / anti-reflection laminate / first adhesive layer / polarizing plate / first phase difference layer / second phase difference layer / panel-side adhesive layer was obtained by making it the same as Example 2, except that the anti-reflection laminate was changed from a TAC film with a phase difference layer attached manufactured by Fujifilm Co., Ltd. (product name: HL214, thickness: 42 μm) to a polycarbonate-based anti-reflection film manufactured by Nitto Denko Co., Ltd. (thickness: 82 μm), and the thickness of the panel-side adhesive layer was changed to the value shown in Table 1.
[0212]
[0213]
[0214] [evaluation]
[0215] As is evident from Table 2, by making the thickness of each adhesive layer 17 μm or less, forming a reinforcing layer between the anti-transparency laminate and the anti-reflection laminate, and making the total thickness of the anti-transparency laminate, the reinforcing layer, and the anti-reflection laminate 200 μm or less, it can be seen that an optical laminate is obtained that satisfies the suppression of orange peel, resistance to localized loads, and suppression of warping under high humidity environments in good balance. Industrial applicability
[0216] The optical laminate of the present invention can be suitably used in an image display device (typically, a liquid crystal display device, an organic EL display device). Explanation of the symbols
[0217] 1 Optical laminate 2 polarizing plates 21 Polarizer 22 protective layer 3. Anti-see-through laminate 31 First entry 32 Anti-see-through layer 4 Anti-reflective laminate 41 Entry No. 2 42 Hard Coat Layer 43 Anti-reflective layer 5 reinforcement layers 61 First adhesive layer 62 Second adhesive layer 63 Third adhesive layer 7. First phase difference layer 8. Second phase difference layer
Claims
Claim 1 An optical laminate comprising a polarizing plate, a first optical functional body bonded to the viewing side of the polarizing plate through a first adhesive layer, a reinforcing layer bonded to the viewing side of the first optical functional body through a second adhesive layer, and a second optical functional body bonded to the viewing side of the reinforcing layer through a third adhesive layer, wherein the thickness of each of the first adhesive layer, the second adhesive layer, and the third adhesive layer is 17 μm or less, and the total sum of the thickness of the first optical functional body, the thickness of the reinforcing layer, and the thickness of the second optical functional body is 200 μm or less. Claim 2 In claim 1, the first optical functional body is a non-transparent laminate, and the non-transparent laminate comprises a non-transparent layer in contact with the first adhesive layer and a first substrate disposed on the visible side of the non-transparent layer and in contact with the second adhesive layer. Claim 3 The optical laminate according to claim 1 or 2, wherein the second optical functional body is an anti-reflective laminate, and the anti-reflective laminate comprises a second substrate in contact with the third adhesive layer, a hard coat layer disposed on the visible side of the second substrate, and an anti-reflective layer disposed on the visible side of the hard coat layer. Claim 4 In claim 3, the anti-reflective layer is located on the outermost surface of the optical laminate, and the moisture permeability of the anti-reflective layer is 0.1 g / mm 2 Optical laminate with less than 100 Claim 5 An optical laminate according to claim 1 or 2, wherein the polarizing plate comprises a polarizer and a protective layer disposed on the viewing side of the polarizer and in contact with the first adhesive layer. Claim 6 In claim 5, the optical laminate has a polarizer thickness of 10 μm or less. Claim 7 An optical laminate according to claim 1 or 2, further comprising a first phase difference layer and a second phase difference layer arranged sequentially from the polarizer side on the side opposite to the viewing side of the polarizer, wherein the first phase difference layer exhibits a refractive index characteristic of nx > ny > nz and the second phase difference layer exhibits a refractive index characteristic of nz > nx > ny.
Citation Information
Patent Citations
Reinforced-type polarizing optical film laminated body for power driving vehicle, and optical display panel in which reinforced-type polarizing optical film laminated body is used
JP2021073500A
Elliptical polarizer
KR1020200022032A
Antireflection film and method for manufacturing the same, and polarizing plate having an antireflection layer formed thereon
KR1020200037413A
polarizing plate
KR1020200103698A
Optical laminate and image display device using the optical laminate
KR1020200115083A
